PENGARUH PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Astuti, Dwi Yuni; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2020)
This scientific to provide evidence of the effect of profitability, liquidity, and solvency on share prices in banking companies on the Indonesian stock The financial ratios the ROA, CR, and DER ratios as independent variables and Share Prices as dependent variable variable for the period 2015-2019. The type of data used is the type of quantitative data in the form of financial statements, and the sampling technique uses purposive sampling. Analysis technique multiple linear regression, using the classic assumption test, t test, and f test. The results of this scientific work indicate that ROA on stock prices with a value of t count 2.691, and t table 2.01290 then t count is greater than t table in the sense of a positive effect. while the CR on the t stock price is 0.410, and the t table is 2.01290, which means negative effect and DER on the stock price with a t value of 0.601, and the t table shows the value of 2.01290, which means negative effect. The results of testing the effect of ROA, CR, and DER have a negative and significant relationship to stock prices with a value of 2,469 and a significance of 0.074